Exploring Codes Mixing of Arabic Language at Islamic Boarding School: A Study on Students’ Daily Communication - Nopriansyah, Beri; Al-farisi, Inqiado; Ramadhani, Gita Fitri (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2024)
This study examines code-mixing phenomena in the oral Arabic communication of students at An-Nur Tangkit Islamic boarding school in Indonesia. Given the relatively recent introduction of Arabic as a foreign language, students often incorporate Indonesian elements into their speech. Through qualitative field research involving observation and interviews, this study investigates the specific forms of code-mixing employed by students and teachers. The analysis reveals three primary language elements in code-mixing: individual words, phrases, and clauses. These findings contribute to a deeper understanding of the linguistic practices and challenges faced by learners of Arabic in Indonesian educational settings.